Comparative Immunogenomics of Canine Natural Killer Cells as Immunotherapy Target - Gingrich, Alicia A.; Reiter, Taylor E.; Judge, Sean J.; York, Daniel; Yanagisawa, Mio; Razmara, Aryana; Sturgill, Ian; Basmaci, Ugur Nur; Brady, Rachel V.; Stoffel, Kevin; Murphy, William J.; Rebhun, Robert B.; et al. (Frontiers in Immunology, 2021)
Natural killer (NK) cells are key effectors of the innate immune system, but major differences between human and murine NK cells have impeded translation. Outbred dogs offer an important link for studies of NK biology and immunotherapy. We analyzed gene expression of putative NK populations from healthy dogs and dogs with naturally-occurring cancers examining differential gene expression across multiple conditions, including steady-state, in vitro activation with cytokines and co-culture, and in vivo activation with inhaled IL-15 in dogs receiving IL-15 immunotherapy. We also compared dog, mouse and human CD3-NKp46+ NK cells using a novel orthologous transcriptome. Distinct transcriptional profiles between NK populations exist between conditions and in vitro versus in vivo treatments. In cross-species analysis, canine NK cells were globally more similar to human NK cells than mice. These data define canine NK cell gene expression under multiple conditions and across species, filling an important gap in translational NK studies.